Angiotensin (1-7) Attenuates Sepsis-Induced Acute Kidney Injury by Regulating the NF-κB Pathway - Zhu, Ying; Xu, Daliang; Deng, Fang; Yan, Yonglin; Li, Jian; Zhang, Chenyu; Chu, Jing (Frontiers in Pharmacology, 2021)
This study explores the protective mechanism of angiotensin (1-7) [Ang-(1-7)] on kidneys by examining its effects on renal histomorphology, inflammatory response, oxidative stress, and NF-κB signaling in mice suffering from sepsis-induced acute kidney injury. A sepsis-induced acute kidney injury mouse model was established by intracervically injecting lipopolysaccharides (LPS group), followed by the administration of Ang-(1-7) [LPS+Ang-(1-7) group]. The serum levels of urea nitrogen, creatinine and cystatin.c were measured with an automatic biochemical analyzer, and changes in proinflammatory cytokines and angiotensin II (Ang II) in the serum and kidneys were quantified by enzyme-linked immunosorbent assays. Changes in oxidative stress indices in the renal cortex were detected by colorimetry. The localization of Ang II in kidneys was examined by immunohistochemistry. Western blotting was used to examine phosphorylated NF-κB-p65 and IκBα levels in kidneys. Compared with the control group, the serum levels of urea nitrogen, creatinine and cystatin.c were increased, whereas the levels of Ang II, TNFα, IL-1β, IL-6, and malondialdehyde (mda) were increased significantly. The levels of Ang II and phosphorylated NF-κB-p65 were elevated in kidneys, whereas the levels of superoxide dismutase (sod), Total antioxidative capacity (TAOC), and inhibitor of NF-κB (IκBα) were reduced in the LPS group (P < 0.05). Pathological damage was also observed in kidneys of LPS-group mice. In Pearson correlation analysis, there was a positive correlation between Ang II and phosphorylated NF-κB-p65 levels, and a negative correlation between Ang II and IκBα levels (P < 0.05). After the application of Ang-(1-7), the levels of urea nitrogen, creatinine, cystatin.c, Ang II, TNFα, IL-1β, IL-6, and mda, as well as the expression of Ang II and phosphorylated NF-κB-p65 in kidneys of LPS+Ang-(1-7)-group mice, were lower than those in kidneys of LPS-group mice, but the levels of sod, TAOC, and IκBα were higher than those of LPS-group mice (P < 0.05). Pathological changes were less severe in mice of the LPS+Ang-(1-7) group. Overall, Ang-(1-7) can decrease the Ang II level, inhibit NF-κB signaling, reduce the inflammatory response, decrease oxidative stress, and mitigate sepsis-associated acute kidney injury.